How do hypothalamic nonapeptides shape youth’s sociality? A systematic review on oxytocin, vasopressin and human socio-emotional development - Torres, N. (2019)
The hypothalamic nonapeptides oxytocin and vasopressin are important modulators of socio-affective behaviours in a wide variety of animal species, including humans. Nevertheless, there is little research addressing their possible roles on socio-affective dimensions of human behaviour across development, during which considerable behavioural and physiological change occurs. Questions still remain about the extent to which findings from adults may directly apply to earlier phases of human development. In this article, we systematically summarize and discuss all existing studies investigating the developmental association of endogenous levels of hypothalamic neuropeptides oxytocin and vasopressin with human social behaviour or on its disruption in paediatric populations. Evidence is sparse insofar as there are still relatively few developmental studies and limited due to correlational research designs and unreliability of methods currently used for neuropeptide measurements in biological fluids. The findings to date generally converge with adult evidence, but also suggest that important differences between age stages may exist. Further studies focusing these differences may prove critical for informing drug development for socio-affective deficits in paediatric populations.